Longitudinal progression of posterior cortical atrophy over 11 years: Relationship between lesion topology and clinical deficits. Issue 8 (14th September 2019) - Kujovic, Milenko; Malikovic, Aleksandar; Jochum, Sarah; Margittai, Zsofia; Lange-Asschenfeldt, Christian; Supprian, Tillmann
ABSTRACT: Posterior cortical atrophy (PCA) is a rare form of dementia primarily characterized by slowly progressing deterioration of visual processing corresponding to atrophy in the posterior parietal and occipital cortices with less prominent memory loss than are usually seen in other forms of dementia such as Alzheimer's Disease (AD). In the present case report, we describe longitudinal data over a period of 11 years regarding clinical and neuropsychological impairments and their relation to the location and extent of cortical changes related to higher order visual processing in a patient with posterior cortical atrophy. In our patient, visual processing deficits concerning space, motion and object perception emerged at the age of 50 and continued to worsen. By the age of 58, while the perception of contrast, color and figure-ground separation appeared undisturbed the patient exhibited pronounced dorsal- and ventral-related visual deficits, which continued to worsen with age. The patient's MRI scans over the course of the disease revealed increasing circumscribed and bilateral atrophy of the parietal and occipital cortices, with a right-sided predominance. The specific localization of cortical atrophy, the slow progression characterized by visual processing deficits and relatively preserved memory were the main criteria for the diagnosis of posterior cortical atrophy. The case report also highlights the importance of an early extensive neurological and neuropsychological evaluation of visual deficits that occur without the presence of ophthalmological disease.